SOA enabled e-administration for institutes providing higher education (International Journal of Engineering and Computer Science, 2014)
The integrative & collaborative value of SOA has benefited industry immensely. The same benefits can and should be provided to the field of Education, especially higher education. The problems of the education sector are:• Lack of customer (student) & service orientation.• Most processes are manual, and hence slow, inaccurate and inefficient.• Processes are not flexible; hence institutions continue to adhere to age-old procedures, which have out-lived their shelf life.• Departments operate in “silos”, where the left hand does not know what the right hand is doing. This leads to inefficiency and a further drop in quality of “educational experience”.These problems can be well addressed by the efficient incorporation of SOA in traditional or present education processes.  This research paper argues that the problems arise because of disconnected & isolated processes and lack of communication between them. This paper focuses on how an ‘Independent IT department’ can manage and run a SOA enabled system to integrate all processes (services) together and make their communication possible. The paper will make the case that SOA has the features to integrate administrative processes of an educational institution. The paper will propose a smoothly coupled set of services which are SOA enabled, and demonstrate the potential to bring the convincing improvement in Academics processes.